An evasion game model for duopoly competition - Eslaminosratabadi, H.; Salimi, M.; Ibragimov, Gafurjan Ismailovich; Amini, M. (Universiti Putra Malaysia Press, 2013)
Based on the Bertrand and Cournot economic models, we develop an evasion game model for a duopoly market with two players competing on price and quantity. We show that if the total financial strength of first mover is greater than that of the second mover, and the first mover observes the second mover perfectly, our proposed optimal strategy can be followed by the first mover to remain the market leader ahead of all competition.